Incidence of pituitary dysfunction following traumatic brain injury: A prospective study from a regional neurosurgical centre. (3rd May 2016) - Alavi, Seyed Alireza; Tan, Chin Lik; Menon, David K.; Simpson, Helen L.; Hutchinson, Peter J.
Abstract: Patients with traumatic brain injury (TBI) may develop pituitary dysfunction. Although, there is now increasing awareness of and investigations into such post-traumatic hypopituitarism (PTHP), the exact prevalence and incidence remain uncertain. Here, we aim to identify the incidence of PTHP in a selected population of TBI patients deemed at risk of PTHP at a regional neurosurgical centre in the UK. A total of 105 patients have been assessed in two cohorts: (i) 58 patients in serial cohort and (ii) 47 patients in cross-sectional late cohort. We found that in serial cohort, 10.3% (6/58) of TBI patients had abnormalities of the pituitary–adrenal axis in the acute phase (Day 0–7 post injury). In comparison, in cross-sectional late cohort, 21.3% (10/47) of the patients developed dysfunction in at least one of their pituitary axes at 6 months or more post-TBI, with hypogonadotrophic hypogonadism being the most common. Twenty-two patients from these two cohorts had their growth hormone assessment at 12 months or more post-TBI and 9.1% (2/22) were found to have growth hormone deficiency. Our results suggest that PTHP is a common condition amongst sufferers of TBI, and appropriate measures should be taken to detect and manage it.